IDENTIFYING FACTORS OF TREE RISK MANAGEMENT FOR LOCAL AUTHORITIES IN SELANGOR - Azlina Mat Salim; Nor Azilah Husin (International Journal of Accounting, Finance and Business, 2021)
The increasing tree risks in Selangor are a sign of unattended issues, lack of maintenance, and absence of standards. The local authorities may keep planting more trees because the intention was to make their city greener or attractive. However, as the Brundtland Commission conceptualized in 1987, "sustainable development" as; paths of human progress which meet the needs and aspirations of the present generation without compromising the ability of future generations to meet their needs; the need to make the environment safe is likely the balance to the core aspiration. This study aims to identify factors of tree risk management. The research explored the relationship between the local governing factors and tree risk management, considered their understanding of the role of tree risk management in governance. These differences shed those six aspects have criteria that are able to affect tree risk management and thus become important factors in managing tree risk in local authorities of Selangor. The research finding suggested the measures and indicators in determining the level of efficiency in the tree risk management of a local leader in Selangor. This study is hoped to offer knowledge contribution to the body of literature in determining the Tree Risk Management to be used by all the local authorities in Selangor